Gambaran Interaksi Obat Pada Pasien Gagal Ginjal Kronik Dalam Proses Hemodialisis - Siti Alfanda Makmur; Madania Madania; Nur Rasdianah (Indonesian Journal of Pharmaceutical Education, 2022)
Chronic Kidney Disease (CKD) is a condition in which there is a decrease in kidney function due to the presence of chronic and irreversible renal parenchyma. Patients with chronic disease often require a combination of several drugs. The administration of drugs combination is generally expected to have a beneficial effect. However, in some cases, drug interactions resulted in ineffective treatment and the emergence of unexpected events. This research aimed to determine drug interactions in patients with chronic kidney disease who are undergoing hemodialysis in the Inpatient Installation of Dr. M.M Dunda Limboto Hospital. This research was observational using a cross-sectional design and retrospective data collection. The sampling technique used was a purposive sampling technique with a total of 51 patient who met the inclusion criteria during the July-Desember 2020 period. Drug interaction data analysis was based on the Drug Interaction Checker and Drug Interaction Facts. The results showed that the most widely used drugs in patients with chronic kidney disease at Dr. M.M Dunda Limboto Hospital were anti-hypertensi drugs (17%), vitamins and minerals (13.30%), and gastrointestinal (11.32%). Drugs interactions with pharmacodynamic mechanisms were 31 cases (53.45%), pharmacokinetics were 21 cases (36.21%), and 6 cases were unknown (10.34%). The level of clinical significance in patients with chronic kidney disease was 75.86% moderate, 13.80% minor, and 10.34% major.